Degradasi Lingkungan Kawasan Wisata Pantai Samas dalam Kajian Ekologi Sosial - Ariza Sandy Najeha; Primantoro Nur Vitrianto (Journal of Tourism and Economic, 2024)
The potential for tourism at Pantai Samas in Bantul, Yogyakarta, is considerable, but the area is currently facing environmental challenges. To address these issues, research has been conducted with the aim of understanding the ecological and social aspects of the region. The findings indicate that environmental degradation can lead to social degradation, and vice versa. For instance, environmental degradation can exacerbate social issues bminimizey limiting access to natural resources, which in turn can cause poverty and food insecurity. Conversely, social and economic pressures can give rise to environmentally destructive practices. This study employed a qualitative approach, encompassing document analysis, field observation, and interviews, to comprehend the behaviors of the local population and the factors that contribute to environmental degradation. Implementing environmental education, sustainable natural resource management, and policies that support social and ecological well-being can help break the cycle of degradation. It is of the utmost importance to implement comprehensive and interdisciplinary solutions that can protect the environment and enhance the socioeconomic conditions of the local community. By adopting preventative measures, such as promoting environmental awareness and maintaining ecological balance, it is hoped that the development of tourism in the Samas coastal area can be sustained and environmental degradation can be minimize. By understanding the behaviors of the local population and the contributing factors to environmental degradation, effective solutions can be developed to rehabilitate the Samas Beach area as a sustainable and integrated tourist destination.